Productividad Versus Género (Journal on studies and research of academic knowledge, 2018)
The present investigation has as main approach the situation that is carried out before the labor productivity and its relation with the gender of the person. For this, the main objective was: Analyze the Productivity of the employee according to Gender; and as Specific Objectives: To establish the increase of productivity according to gender in the public and private administration of the city of Encarnación. Determine the benefits of gender equality, for productivity, and finally; Identify the benefits of a good Organizational Climate. The methodology used for this research was mixed, analytical level, to collect data was conducted survey of students of the Faculty of Economic and Administrative Sciences of the UNI. It is determined as a closure of the research that productivity is necessary and effective relationship with gender, and that its applicability is necessary to achieve a more equitable and just world.
Keywords: Productivity; Gender; equality